A new polymer field effect transistor based on fluorene derivative with fused furan rings. Issue 44 (7th August 2018) - He, Yang; Xiao, Mingchao; Liu, Ye; Zhang, Xi; Jiang, Lang; Liu, Hui; Zou, Yingping
ABSTRACT: Composed of novel monomer (10, 10‐dihexyl‐10‐fluoreno[2, 3‐b:7, 6‐b′]difuran‐2, 7‐diyl)bis(tri‐methylstannane) (DFF) and commercial 2, 5‐di(2‐ethylhexyl)‐3, 6‐di(5‐bromothiophen‐2‐yl)diketopyrrolopyrrole (DPP32), PDFFDPP32 is synthesized and systematically characterized by high‐temperature gel‐permeation chromatography, thermogravimetric analysis, ultraviolet–visible absorption, Fourier transform infrared spectroscopy, and cyclic voltammetry testing. The resulting polymer displays good hole transport behaviors in bottom gate/top contact organic field effect transistors (OFET) with hole mobility up to 6.42 × 10 −3 cm 2 V −1 s −1 . The rough surface morphology of the polymer films is characterized by atomic force microscopy, and the polymer films are in an amorphous state, as demonstrated by X‐ray diffraction. The intra‐ and interchain O···S noncovalent interactions, as verified by X‐ray photoelectron spectroscopy, possibly endow the polymer with enhanced interactive forces among the polymeric chains. The results indicate that PDFFDPP32 has potential applications in OFET, and the novel monomer DFF has prospects for building high‐performance organic optoelectronic materials. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46865 Abstract : Synthetic routes of polymer and noncovalent interactions among polymer chains